SOSIALISASI RISIKO LIMBAH MINYAK JELANTAH DAN SOLUSINYA - Wahyuni, Fitri; Nisa, Rasya Aulia Nathania; Julian, James; Lumbantoruan, Regina Natalindah; Mahdhudhu, Fathin Muhammad; Purba, Riki Hendra; Armadani, Elvi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Used cooking oil is cooking oil that is no longer suitable for use because it has undergone changes in physical and chemical properties during the frying process. Used cooking oil is a hazardous and toxic waste; consuming it can cause negative impacts on health and disposing of it carelessly can cause environmental pollution. However, public knowledge about the dangers and impacts of used cooking oil is still minimal. A study showed that there are still many people who dispose of used cooking oil on the ground and waterways. Therefore, the activity designed by the PKM team of Universitas Pembangunan Nasional Veteran Jakarta aims to increase public knowledge about the dangers and impacts of used cooking oil and provide solutions to reduce the pollution of used cooking oil waste. This activity was carried out in the Grand Pakis Residence housing complex using socialization and training methods. In this activity, the PKM team invited representatives from the Jalantara foundation as speakers to explain the impact of used cooking oil on the environment and health to the community. Not only that, the community was also given a training on processing used cooking oil into other products as a solution to reduce used cooking oil waste. The result of this activity is that the knowledge of residents about the dangers of used cooking oil for the environment and health has increased by 80.95%. In addition, the residents also know how to reduce used cooking oil by turning it into useful products such as soap.